The clinical implementation of non‐invasive prenatal diagnosis for single‐gene disorders: challenges and progress made. (17th May 2013) - Lench, Nicholas; Barrett, Angela; Fielding, Sarah; McKay, Fiona; Hill, Melissa; Jenkins, Lucy; White, Helen; Chitty, Lyn S.; Chitty, Lyn S.; Bianchi, Diana W.
ABSTRACT Recently, we have witnessed the rapid translation into clinical practice of non‐invasive prenatal testing for the common aneuploidies, most notably within the United States and China. This represents a lucrative market with testing being driven by companies developing and offering their services. These tests are currently aimed at women with high/medium‐risk pregnancies identified by serum screening and/or ultrasound scanning. Uptake has been impressive, albeit limited to the commercial sector. However, non‐invasive prenatal diagnosis (NIPD) for single‐gene disorders has attracted less interest, no doubt because this represents a much smaller market opportunity and in the majority of cases has to be provided on a bespoke, patient or disease‐specific basis. The methods and workflows are labour‐intensive and not readily scalable. Nonetheless, there exists a significant need for NIPD of single‐gene disorders, and the continuing advances in technology and data analysis should facilitate the expansion of the NIPD test repertoire. Here, we review the progress that has been made to date, the different methods and platform technologies, the technical challenges, and assess how new developments may be applied to extend testing to a wider range of genetic disorders. © 2013 John Wiley & Sons, Ltd.